Calibration setting numbers for dose calibrators for the PET isotopes 52Mn, 64Cu, 76Br, 86Y, 89Zr, 124I. (July 2016) - Wooten, A. Lake; Lewis, Benjamin C.; Szatkowski, Daniel J.; Sultan, Deborah H.; Abdin, Kinda I.; Voller, Thomas F.; Liu, Yongjian; Lapi, Suzanne E.
Abstract: For PET radionuclides, the radioactivity of a sample can be conveniently measured by a dose calibrator. These devices depend on a "calibration setting number", but many recommended settings from manuals were interpolated based on standard sources of other radionuclide(s). We conducted HPGe gamma-ray spectroscopy, resulting in a reference for determining settings in two types of vessels containing one of several PET radionuclides. Our results reiterate the notion that in-house, experimental calibrations are recommended for different radionuclides and vessels. Highlights: Dose calibrators measure radioactivity by ionization of gas from emitted radiation. Accuracy of dose calibrators depends on "calibration setting numbers" for isotopes. Many manufacturer settings are interpolated from emissions of other radionuclides. As a high-precision reference, HPGe gamma-ray spectroscopy was conducted. New calibrations were found for PET isotopes 52 Mn, 64 Cu, 76 Br, 86 Y, 89 Zr, and 124 I.